In vitro bioactivity of novel chitosan/gelatin/halloysite nanostructured coatings on anodised titanium via electrophoresation for bone implant - Alipal, Janifal (2022)
Electrophoretic deposition (EPD) involves coating densification via matrix micro/nano-filling on a template-assisted substrate. This mechanical interlock technique has recently been used to avoid coating cracking and delamination. This thesis reports that EPD organic-inorganic nanostructured coatings containing chitosan/gelatin hydrogel and halloysite nanotubes (HNTs) produce an ideal mechanical interlock. In the proposed bio-composite, HNTs are used to densify the coating's mixture. The mechanical interlocking of the proposed bio-composite coating defines its net mechanistic bioactivity. Prior to EPD, the study goes through a substrate pre-processing step in which the cp-Ti surface is modified using micro-arc anodic oxidation (MAO) in a CaP-based electrolyte (a mixture of β-glycerophosphate and calcium acetate). The study discovered that anodised titanium (MAT) in donut-shaped morphology (MAO 350 V) has better mechanical stability and osteogenic cellular response compared to the needle-like structure. The findings determined that the donut-shaped MAT microstructure is the best next choice for the EPD substrate in the coating mechanical interlock study. Despite the fact that the EPD processing parameters were varied (10-30 V; 5-20 min), the mechanically interlock nanostructured coating (template-assisted EPD) significantly improved coating adhesion and osteogenic development in this study. In coating fabrication, the weight fraction of HNTs in the hydrogel is critical, and this study determined that the optimal composition of a steric stabilised organic-inorganic EPD suspension for chitosan/gelatin/HNTs is 6:14:12 g/L. Modifying implant surfaces using novel techniques such as varying substrate morphology and/or degraded coatings has become a popular method for improving implant osseointegration. This recent study established that specific surface features influence how bone cells interact with a material and which specific surface features result in optimal bone integration. In this thesis, MAT is designed to be a highly bioactive EPD substrate, resulting not only in a highly stable coating structure but also in improved osteogenic development, specifically osteoblast mineralisation and differentiation.